Well-posedness of transonic characteristic discontinuities in two-dimensional steady compressible Euler flows - Chen, G; Kukreja, V; Yuan, H (2013)
In our previous work, we have established the existence of transonic characteristic discontinuities separating supersonic flows from a static gas in two-dimensional steady compressible Euler flows under a perturbation with small total variation of the incoming supersonic flow over a solid right wedge. It is a free boundary problem in Eulerian coordinates and, across the free boundary (characteristic discontinuity), the Euler equations are of elliptic-hyperbolic composite-mixed type. In this paper, we further prove that such a transonic characteristic discontinuity solution is unique and L-stable with respect to the small perturbation of the incoming supersonic flow in Lagrangian coordinates. © 2013 Springer Basel.